Curso para elaboração de projeto de pesquisa como proposta metodológica para a iniciação científica no contexto da educação profissional e tecnológica - Santos, Emanuele Eralda Pimentel (Instituto Federal de Educação, Ciência e Tecnologia do Tocantins, 2021)
The present work results of a master's research in education of the Program of Post Graduation in Professional and Technological Education (ProfEPT). The objective of this work was to offer a course for the elaboration of scientific research projects, intitled: “Research now”, given in such a way in the face to face modality how much online, searching, through questionnaires, to understand the importance of the research and the scientific initiation for the integral formation of the students of the Federal Institute of Tocantins (IFTO) - Palmas Campus. Therefore, intention research was carried through having invited the students to carry through the course, the application of the activity properly said, the evaluation of the results through comparison with the intended research, and the verification of the interest of these students after the activity. The course was structuralized in an accessible language to secondary education, in the light of the theory of the didactic transposition proposal for Yves Chevallard and of the guiding principles of the Professional and Technological Education (EPT). The proposal of education of “Research now” was applied to the entailed students to Integrated Secondary Education of the IFTO – Campus Palmas in accordance with the stages that compose a scientific research project. At the end of it, a comparative evaluation was carried out (before and after) to assess the students' perception of the proposed educational product and on the elaboration of the scientific research project after having known both more deeply. The applied methodology was quanti qualitative. The data were obtained through the use of questionnaires and analyzed by the categorization method. The research of intention in participating in the course for the elaboration of the research project identified the necessity of the students to be instigated to participate in research incentive programs. So that the learning could construct its proper projects, it was applied “Research now” to 60 students being that the construction of the projects was concluded by nineteen students in the face-to-face modality and eight in the online modality. As final considerations, emphasizes the importance of the entire academic community at the programs of incentive to the research in the on school scope is stood out it, given the reaction positive and familiar of the students after the application of the Educational Product. Overall, it was distinguished relevance of the paper of the teacher in the direction to develop didactic and methodological teaching proposals of education that instigate the students to the practical one of the research, since secondary education, requiring, for in such a way, autonomy, creativity and disciplines, characteristics that they need to be stimulated along the student path.